Aplikasi Abu Daun Mahoni pada Beberapa Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Okra (Abelmoschus esculentus L.) - Yono Putra; Idwar Idwar; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Okra is highly nutriuos vegetables which can be developed in Riau with using Histosol and Ultisol land by addition Mahogany leaf ash. The aim of this research is to find out the influence of Mahogany leaf ash on medium Histosol, Ultisol, and the mixture and obtain best dose for each medium to growth and yield of Okra plants. The experiment was conducted in Experimental Field of Faculty of Agriculture, Riau University, in Mei until September 2018 experiments multiplied with 3x4 factorial arengged according to Nested design (Nested). The first factor was application various medium, namely Histosol, Ultisol the mixture (1:1). The second factor was addition several ash doses, namely 0,25 recomended dose, 0,5 recomended dose, 0,75 recomended dose and 1 recomended dose (Histosol = 6 ton.ha-1, Ultisol = 12 ton.ha-1, and the mixture = 9 ton.ha-1). The result of this reasearch showed addition several ash doses on various medium has not significant to almost all parameter except stem diameter. The Addition of recomended ash dose on medium Histosol only increas fruits yields 15,66% with weights 150,17 g, medium Ultisol 32,55% with weights 114,00 g, and the mixture 29,17% with weights 121,00 g compared with addition 0,25 recomended dose.Keywords: Okra, Ash, Histosol, Ultisol